The priests and the descendants of Levi in the book of Malachi - Weyde, K. W. (Faculty of Theology, University of the Free State, 2015)
The article argues that the phrase “the descendants of Levi” in Mal 3:3 includes both priests and Levites and that the author of the book of Malachi was an inspired temple preacher, or writer, who probably belonged to the ranks of priests or Levites. He was a voice of the late 5th century, who with prophetic authority, like his predecessors, the earlier prophets, among others criticised the priests’ misconduct of the sacrificial cult (Mal 1:6–2:9). For this reason, he rejected the offerings. The failure of the priests corrupted the whole sacrificial cult including those responsible for it, the descendants of Levi, who for this reason had to be purified. The message related in Mal 3:1‑4 conveys that YHWH’s coming messenger will carry out this purification. Then the descendants of Levi will conduct the sacrificial cult in accordance with the regulations of the law, as in the days of old.
Keywords: Old Testament cult; Descendants of Levi; Purification; Authorship of Malachi; Prophets